⁠From liver to cardiovascular system: the MASLD–ASCVD continuum - Andrea Boccatonda; Antonella Bray; Marialuisa Sveva Marozzi; Alessia Cipollone; Gianfranco Lauletta; Damiano D’Ardes; Sebastiano Cicco; Francesco Cipollone (Internal and Emergency Medicine, 2026)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most prevalent chronic liver disease worldwide and is increasingly recognized as a systemic cardiometabolic disorder. Atherosclerotic cardiovascular disease (ASCVD) represents the leading cause of mortality in patients with MASLD. This review aims to summarize current evidence on the epidemiology, pathophysiological mechanisms, and clinical impact of MASLD on cardiovascular outcomes. We reviewed epidemiological studies, mechanistic investigations, imaging-based analyses, and large population-based cohorts evaluating the association between MASLD and cardiovascular disease, with particular attention to major adverse cardiovascular events, subclinical atherosclerosis, cardiac dysfunction, arrhythmias, and thromboembolic complications. MASLD is associated with an increased risk of ischemic heart disease, stroke, heart failure, atrial fibrillation, peripheral artery disease, and venous thromboembolism; in several cohorts, this association persists after adjustment for traditional CV risk factors, although residual confounding and population heterogeneity should be considered. Liver fibrosis severity consistently emerges as a major modifier of CV risk. Pathophysiological mechanisms linking MASLD to ASCVD include insulin resistance, atherogenic dyslipidemia, chronic low-grade inflammation, oxidative stress, endothelial dysfunction, prothrombotic alterations, and dysregulation of the gut–liver–heart axis. These shared pathways support a bidirectional relationship in which hepatic steatosis both reflects and amplifies systemic cardiometabolic injury. MASLD should be regarded as a CV risk enhancer rather than a liver-confined disease. Early identification of MASLD, assessment of fibrosis burden, and integrated cardiometabolic management are essential to improve long-term outcomes. Future studies should determine whether targeted treatment of MASLD translates into sustained reductions in CV morbidity and mortality.